Rhododendron mingii (Ericaceae), a new species from Southeast of Yunnan, China - Liu, Zhenwen; Liu, Ende; He, Deming; Ma, Yongpeng; Gao, Lianming (Phytotaxa, 2023)
A new species of Rhododendron, R. mingii (Ericaceae), from Malipo County, Southeast of Yunnan, China is described and illustrated here. Morphologically, the new species is most similar to R. genestierianum but differs by its much shorter petiole and leaf, hairs along the margin of the leaf, densely white powder on outer surface of petal, and slender and erect style. A molecular phylogenetic analysis based on three standard DNA barcodes (rbcL, matK and ITS) indicates that R. mingii is a distinct lineage that genetically differs from R. genestierianum.